RELACIÓN SER HUMANO-NATURALEZA: DEBATIENDO EL DESARROLLO SOSTENIBLE DESDE LA FILOSOFÍA DE LA CIENCIA - Diosey Ramón Lugo-Morin; Larry M. Frolich; Teresa Magal-Royo (European Scientific Journal, ESJ, 2015)
The global ecological-economic dynamic tends to foment a false dichotomy between human beings and nature. This logic has generated a debate over the role of interdisciplinary approaches to eco-social studies. With an eye towards enriching this debate we propose a theoretical reflection on the human-nature relation y how emergent interdisciplinary connections provide a response in a society undergoing constant change.